Transforming Science Education through Gamification: A Systematic Analysis of Trends, Impacts, and Implications - Zarror, Afif Fauzan; Sumaryati, Sri; Sukmawati, Fatma (Universitas Muhammadiyah Surakarta, 2025)
The increasing need for engaging and effective science education has prompted educators to explore alternative instructional strategies. Gamification, the integration of game elements into learning environments, has emerged as a promising approach to enhance student motivation, participation, and conceptual understanding. This study aims to systematically examine how gamification has been implemented in science education across diverse contexts and educational levels. A systematic literature review was conducted using a structured protocol to identify relevant open-access articles published between 2021 and 2025. A total of ten empirical studies were selected based on predetermined inclusion criteria. The results reveal four dominant forms of gamification: educational card games, scenario-based simulations, digital escape rooms, and serious games addressing contemporary science issues. These interventions were applied in various science disciplines, including chemistry, microbiology, anatomy, nutrition, and environmental education. The findings highlight positive cognitive, affective, social, and motivational impacts on learners. Despite challenges such as limited digital access and varying teacher readiness, gamification proves to be an adaptable and impactful pedagogical tool. This review concludes that gamification, when thoughtfully designed, supports meaningful science learning and fosters broader scientific literacy.